Potassium-promoted Ce0.65Zr0.35O2 monolithic catalysts for diesel soot combustion - Neyertz, Claudia A (2014)
This work presents a comparative study of Ce0.65Zr0.35O2 and CeO2 catalysts supported on cordierite for soot combustion, and the effect of potassium on the catalytic performance. The catalysts were prepared by sequential impregnation over the monolith. The activity in the soot combustion by O2 was studied by successive temperature programmed oxidation cycles, using a loose-contact mode between the soot and the catalyst. A deactivation was observed after ten cycles of combustion for potassium catalysts. This deactivation was attributed to potassium loss at high temperatures. On the other hand, the catalysts without K showed activation after the ten soot combustions. When catalysts with the same cerium molar loading were compared, an improvement in the activity of the mixed oxide compared with the pure ceria was observed. The soot combustion was improved for K/Ce0.65Zr0.35O2/cordierite and K/CeO2/cordierite with NO/O2 presence. However, the catalyst K/CeO2/cordierite was still more active. By X-ray diffraction analyses, it was found that insertion of zirconium into the CeO2 structure took place during preparation. However, a Raman and SEM/EPMA studies indicated heterogeneity in Ce0.65Zr0.35O2. Domains of cerium–zirconium inside the cordierite channel with a ratio different from the nominal value were observed by scanning electron microscopy analyses. This heterogeneity could decrease the catalytic activity of the cerium–zirconium oxide mixture. The catalytic activity in supported catalysts strongly depends on the effect of Zr, the number of Ce4+/Ce3+ redox surface sites, the BET area and the structural changes induced by high temperatures.